2014
DOI: 10.5603/fm.2014.0025
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial bridge and coronary arteries: morphological study and clinical significance

Abstract: Myocardial bridge (MB) is the myocardial bundles covering a segment of a coronary artery or one of its branches. This work aimed to (Folia Morphol 2014; 73; 2: 169-182)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…The lack of correlation between the type of vascularization and localization of myocardial bridges was confirmed in the studies of Bharambe and Arole (40). Ashraf and Nasr (38) came to the same conclusions and point out that 77.8% of myocardial bridges were on the left coronary artery, without a significant difference in regard to the type of vascularization, which is in accordance with the results of this study, where of a total 33 myocardial bridges, 25 (75.76%) were localized to the left coronary artery.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The lack of correlation between the type of vascularization and localization of myocardial bridges was confirmed in the studies of Bharambe and Arole (40). Ashraf and Nasr (38) came to the same conclusions and point out that 77.8% of myocardial bridges were on the left coronary artery, without a significant difference in regard to the type of vascularization, which is in accordance with the results of this study, where of a total 33 myocardial bridges, 25 (75.76%) were localized to the left coronary artery.…”
Section: Discussionsupporting
confidence: 88%
“…The results of this study have indicated that the incidence of arterial vascularization types is approximately same in the heart group with myocardial bridges as well as in the group without them, so it is established that there is no correlation between the presence of myocardial bridges and the type of arterial vascularization of the heart. Up to the same conclusion came Luis Erresto and his associates who investigated the Colombian population (37), as well as Ashraf and Nasr (38) among the Saudi population. However, these results are opposite to the results of Loukas and associates (39) who state that among the hearts with present myocardial bridges, the left type of vascularization is most common, in 66.6% of cases, while the right type is represented by only 24.6%.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…By analyzing their references, we found another 16 potentially relevant articles that were also downloaded. From the 203 articles, 120 were included in the final analysis of prevalence. Details about search synthesis are presented in Figure S1.…”
Section: Resultsmentioning
confidence: 99%
“…It is difficult to say with certainty what characteristics of a bridged segment predispose it to being symptomatic. Length and depth have been proposed as important features, with segments that are at least 2–3 mm deep and 20–30 mm long contributing to more symptoms ((20), (71). Bridging is also seen very commonly in individuals with hypertrophic cardiomyopathy, but it is unclear if negative outcomes are related to the cardiomyopathy itself or the bridged segment.…”
Section: Discussionmentioning
confidence: 99%